A5 4 It’s Raining Tiplers - Morriss, Luke; Matkin, Eleanor; Shkullaku, Marin (Physics Special Topics, 2023)
This paper calculates the number of falling Tiplers that are required to break apart the Earth and the Moon, assuming that all the kinetic energy of the books is absorbed by the Earth and the Moon upon impact. We find that 1.98 × 10^29 falling Tiplers are required to break apart the Earth, and 4.372 × 10^23 falling Tiplers are required to break apart the Moon, which are many orders of magnitude greater than the number of books published, making these situations astronomically implausible.